PENINGKATAN KEMAMPUAN MEMECAHKAN MASALAH MELALUI PEMBELAJARAN THINK PAIR SQUARE SHARE BERBANTUAN LEMBAR PESAN BERMAKNA - Navianto, Andi (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2021)
Researchers often find students confused about starting the first step in solving problems. Students are less able to use the available information and knowledge that has been learned as a basis for solving problems. In addition, students' efforts to solve problems through discussion and establish communication with other students are still low. This study aims to describe efforts to improve problem-solving skills using Meaningful Message Sheets in Think Pair Square Share cooperative learning in class IX-A students of SMP Negeri 3 Pule in the 2017/2018 school year. The research subjects were 30 students. This classroom action research has been carried out in two cycles. Each cycle consists of two meetings. The data collected were student activity sheets and test results. The stages of this research consist of planning, implementation, observation, and reflection. The use of Meaningful Message Sheets in Think Pair Square Share (TPSS) cooperative learning can improve problem solving skills in class IX-A students of SMP Negeri 3 Pule in the 2017/2018 academic year. This is indicated by an increase in student activity and test results. The results of student activities have increased from the Enough category in the first cycle to the Good category in the second cycle. Student test results showed an increase in class completeness from 17% in the first cycle to 87% in the second cycle with an average score of 79.